Effect of alpine ski boots on lower limb movement during jumping - Nakazato, K.; Takahashi, S.; Sasadai, J.; Ishige, Y. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study aimed to investigate the effects of alpine ski boots (ASB) on lower-limb power generation for movements such as jumps. Seven male alpine ski racers participated in this study and performed counter movement jumps and squat jumps. All trials were recorded using a motion capture system and two force plates. The jump height in the ASB condition was significantly lower than that in the training shoe (TS) condition for both jumps. The range of motion of both the ankle and knee joints in the ASB condition significantly decreased for both jumps. The angular velocity at hip joint extension in the ASB condition was significantly higher than that in the TS condition for both jumps. Our findings revealed that lower-limb movement and power are restricted when wearing ASB, and suggested the importance of power transfer training using the hip joint while wearing an ASB.